Tactical planning in soccer: general aspects and specific aspects - Otávio Baggiotto Bettega; Larissa Rafaela Galatti; Antonio Guilherme Schmitz Filho; Alexandre Bobato Tozetto; Benjamín Longarela Pérez; Alcides José Scaglia (Federación Extremeña de Balonmano; University of Extremadura, 2016)
The tactical planning in soccer should primarily base its constitution in the gaming functionality, considering both general and specific aspects, as well as factors outside the procedural terms of the game. In this way, the bibliographic and descriptive study aims to point out important principles for structuring a tactical planning in soccer, highlighting key components in this process. The general aspects related to the club´s philosophy and working conditions conducted in accordance with specific aspects of the game's tactical nature are extremely important in structuring the planning. Therefore, understanding the game goes beyond its internal specificity, transcending to its other external aspects.